Accelerating Economic Transformation through Strengthening Halal Food Downstream Competitiveness for National Resilience - Euis Amalia; Muhammad Hanafi (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: This study explores the integration between food downstreaming and the halal industry through value chain integration theory, industry competitiveness concept and astagatra national resilience perspective. Study Design/Methodology/Approach: The research was conducted using a qualitative descriptive method. Data were collected through systematic literature analysis and interviews with various experts in the fields of economics and wealth sources. The descriptive-analytical analysis was conducted using the framework or concepts of Porter's diamond model, CRT, SWOT (EFAS and IFAS), and TOWS. Findings: The Porter's Diamond Model analysis indicates that the halal food downstreaming industry in Indonesia is not yet fully competitive, with the CRT analysis identifying four root causes. Then, based on the SWOT analysis, the coordinates (2.43; 2.78) were obtained, indicating the need for a